Contribution of the early-established plant hierarchies to maize crop responses to N fertilization - Rossini, Maria de Los Angeles (2018)
Maize crop production depends on nitrogen (N) availability, N uptake by the crop and the efficiency with which absorbed N is used to produce biomass (NUEBIOM) or grain yield (NUEGRAIN). This framework assumes unique efficiency values for the whole stand, with no distinction among plants in spite of the inherent inter-plant variability of plant growth, especially under crowding stress. In this work we assessed the degree of contribution of different early-established groups of plants to crop responses to N fertilization of two maize hybrids (H) with different tolerance to crowding stress (high for AX820 and low for AX877) cultivated at two stand densities (9 and 12 pl m−2). Groups corresponded to the lower, mid and upper terciles (Ts) of the crop, representing dominated, intermediate and dominant plants, respectively. In most cases, lower and mid Ts had a greater participation in crop biomass and grain yield responses to N fertilization. The response of NUEBIOM and NUEGRAIN to N fertilization was higher for the lower and mid Ts than for the upper T. For each N level, crop NUEGRAIN was negatively related to inter-plant variability in plant NUEGRAIN. When no N was added, the reduction in crop NUEGRAIN of both hybrids was mainly caused by the increased inter-plant variability in plant N uptake (i.e. resource capture). Additionally, the crowding-intolerant AX877 under the most stressful condition (12 pl m−2 and no added N) had a reduced crop NUEGRAIN due to the enhanced plant-to-plant variability in grain yield (i.e. resource use). Consequently, the early-established plant-to-plant variability pattern conditioned crop NUEGRAIN; the predominant path was hybrid dependent.